A neutronic investigation of tristructural isotropic-duplex fuel in a high-temperature reactor prismatic seed-and-blanket fuel block configuration with reduced power peaking - Rabir M.H.; Ismail A.F.; Yahya M.S. (John Wiley and Sons Ltd, 2023)
Combustion; Fuels; High temperature engineering; Monte Carlo methods; Oxide minerals; Thoria; Uranium dioxide; High temperature engineering test reactors; Monte carlo n particles; Multiplication factor; Neutron flux distributions; Neutronic analysis; Power Optimization; Reactor modeling; Reference modeling; High temperature reactors